2018
DOI: 10.1159/000493785
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Phase Plasma PCSK9 Levels and Recurrent Cardiovascular Events in a Chinese Acute Myocardial Infarction Cohort

Abstract: Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a promising target for lowering plasma low-density lipoprotein cholesterol and preventing cardiovascular (CV) disease. Whether plasma PCSK9 measured during the acute phase predicts recurrent CV events in patients with acute myocardial infarction (AMI) remains unresolved. Methods and Results: Plasma PCSK9 levels were measured in 1,646 patients with AMI from the China PEACE-Prospective AMI Study at the acute phase. Additionally, 248 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
13
1
Order By: Relevance
“…After we screened titles and abstracts, 29 articles were qualified for full-text evaluation. After full-text review, nine studies were excluded, and 22 eligible cohorts from 20 eligible articles were finally included for metaanalysis (7)(8)(9)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Figure 1 demonstrates a flowchart for the study selection.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…After we screened titles and abstracts, 29 articles were qualified for full-text evaluation. After full-text review, nine studies were excluded, and 22 eligible cohorts from 20 eligible articles were finally included for metaanalysis (7)(8)(9)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Figure 1 demonstrates a flowchart for the study selection.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Of the 11 studies included, only 1 ( 22 ) was a retrospective cohort study and the others were prospective cohort studies, with a publication period from 2014 to 2020. Four trials ( 20 , 22 , 27 , 28 ) reported RRs according to continuous concentrations of PCSK9, three studies ( 19 , 24 , 26 ) reported RRs according to categorical levels, and four studies ( 8 , 21 , 23 , 28 ) reported RRs according to both continuous and categorical levels. We included 8,471 patients, and the sample size of each study ranged from 249 to 2,030.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the characteristics of the included studies (8,9,(19)(20)(21)(22)(23)(24)(26)(27)(28). Of the 11 studies included, only 1 ( 22) was a retrospective cohort study and the others were prospective cohort studies, with a publication period from 2014 to 2020.…”
Section: Study Selection and Patient Populationmentioning
confidence: 99%
“…29,30 The current study's strength was that the recruited subjects were better identified as a high-risk population, which is entirely different compared with other studies. 10,11,13,31 Moreover, this has been the first study to determine the association between PCSK9 E670G and R46L polymorphisms and MACCE among patients with STEMI undergoing primary PCI. Given that the current study was a single-center prospective cohort observational study and not a nationwide study, its selected population attending the tertiary hospital can be considered a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study did not predict cardiovascular disease (CVD) recurrence during the 1-year follow-up period. 10 Our present study recruited only patients with STEMI, all of whom were managed with primary PCI as recommended by our medical care standards.…”
Section: Discussionmentioning
confidence: 99%